THE EFFECT OF SELF-LEADERSHIP, SELF-ABILITY AND RESILIENT ON THE PERFORMANCE OF SURABAYA SATRESKRIM POLICE INVESTIGATORS THROUGH ORGANIZATIONAL COMMITMENTS AS INTERVENING VARIABLES - Fitri Purwanto; Siti Mujanah; Sumiati Sumiati (UNUSA Press, 2022)
This study aims to prove and analyze the effect of self-leadership, self-ability and resilient on organizational commitment and performance of the investigators. The sample used is 90 respondents who are investigators in Satreskrim (Criminal Investigation Agency) in Surabaya devision. The data was taken through a Survey technique with a questionnaire instrument and data were analyzed using PLS (Partial Least Square). The results of this study showed that the self-leadership, self-ability and resilient have significant effect on the investigator's commitment and performance, while commitment has a significant effect on investigator performance. This indicates that as an investigator, they must have self-leadership, self-ability, and high resilience, so that they can achieve the targets that have been set